(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper explores the practice of teaching theory, and especially reasoning of education, in an advanced education context. The purpose of this paper is to present a system for educational programs elucidation and design that mirrors the approach of theory in education as an embodiment of deep rooted learning and trans-developmental reasoning. Especially as a point of reference in identifying the focal ideas to be comprehended inside educational modules, and as a process by which more profound learning and intellectual commitment might be overseen and facilitated.